Development of “Gatot Kaca Berburu Bilangan” Edugame Based on Construct 2 to Improve Elementary Students' Understanding of Odd and Even Numbers - Haryono, Mukhamad Janji; Rufi’i; Rahmatullah, Reza (UNDIKMA, 2025)
Mathematics is often perceived as an abstract subject by elementary school students, particularly when learning concepts such as odd and even numbers. This research aims to develop an interactive edugame titled “Gatot Kaca Berburu Bilangan” using Construct 2, an HTML5-based game engine, to enhance conceptual understanding among second-grade students. The development process follows the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), involving expert validation, student trials, and quantitative testing. The game incorporates local cultural elements through the character Gatot Kaca, aligning with students' visual and kinesthetic learning styles. Validation from subject matter and media experts shows a high feasibility level, while trials reveal increased motivation, engagement, and significant improvements in student learning outcomes. A paired sample t-test indicates a statistically significant difference between pre-test and post-test scores (p < 0.05). Students demonstrated greater interest and enthusiasm, supporting the game’s effectiveness not only cognitively but also affectively and socially. This study concludes that edugames such as “Gatot Kaca Berburu Bilangan” can serve as innovative, culture-integrated learning media that effectively support early-grade mathematics education.